IMPLEMENTASI SUPERVISI AKADEMIK KEPALA MADRASAH DI MA AZIZAH DARUSSALAM PALEMBANG - Pungut; Cipto Handoko; Sunarto (UNISAN JURNAL, 2022)
This study aims to see how the implementation of academic supervision of headmaster during the pandemic. This research was conducted using qualitative methods with the type of phenomenological research. The research was conducted at MA DARUSSALAM Palembang , Na IX-X District, North Labuhanbatu Regency, Academic Year 2020-2021. Data collection was carried out by interview, observation and documentation. The subjects of this study were the headmster, the deputy head of the madrasah in the field of curriculum, and teachers in the field of study. The implementation of the academic supervision of headmaster is carried out in three cycles, namely cycle 1 in the form of a contract, cycle 2 in the form of implementation, and cycle 3 in the form of strengthening. The results showed that the implementation of academic supervision of headmaster during the pandemic was going well. Although the learning uses a weekly class shift system, it does not reduce the enthusiasm of the headmaster to continue to improve the quality of the teaching and learning process at SMP It Darul Mukhlasin Palembang . Teaching and learning activities at MA Darussalam Palembang are conducted face-to-face with a system of alternating classes every week. MA Darussalam Palembang is in the green zone so that it was allowed by the task force team Regency to carry out face- to-face teaching and learning activities.